Microstructure evolution in γ-irradiated carbon fibers revealed by a hierarchical model and Raman spectra from fiber section. (17th June 2016) - Sui, Xianhang; Xu, Zhiwei; Hu, Chuansheng; Chen, Lei; Liu, Liangsen; Kuang, Liyun; Ma, Meijun; Zhao, Lihuan; Li, Jing; Deng, Hui
Abstract: The surface activity and mechanical properties of carbon fibers (CFs) were improved simultaneously by magical γ-irradiation. However, microstructure evolution rules of γ-irradiated CFs were still ambiguous. As a representative, T1000 CFs were irradiated by γ-rays and then observed by X-ray diffraction, X-ray photoelectron spectroscopy and Raman spectroscopy from fiber surface, deducing the paradoxical results in terms of fiber structural transformation due to the different penetration depth of above measurements. Therefore, a hierarchical model composed of outer-surface, sub-surface and core parts had been proposed, which allowed us to understand the microstructure evolution of irradiated CFs profoundly. Subsequently, Raman spectra from fiber cross-section were performed to further confirm the accuracy of new model. The results demonstrated that oxygen-containing functional groups were significantly introduced into the outer-surface by the combined effect of γ-rays and reactive media, which increased the surface activity and disordered the structure of outer-surface part. Meanwhile, γ-irradiation improved the graphitic order and atomic rearrangement of sub-surface and core parts regardless of medium effect. Furthermore, the graphitization of sub-surface part showed more notable increase than that of core part under γ-irradiation. This paper would offer the key to reveal the relationship among microstructure, surface activities and mechanical properties of γ-irradiated CFs.